Pengembangan Model Physical Activity Berbasis Multimedia Interaktif Untuk Anak Usia 10-12 Tahun - Abdullatif Sidiq; Ruslan Abdul Gani; Febi Kurniawan (Jurnal Porkes, 2026)
The low levels of physical activity among elementary school-aged children, resulting from the prevalence of gadget use and the continued reliance on conventional physical education instruction, form the background of this study. The study aims to develop an interactive multimedia-based physical activity model for children aged 10–12 years and to test its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, followed by a quasi-experimental test with a non-equivalent control group. The study subjects consisted of 80 students from three schools. The instruments included a validation sheet, a basic motor skills test (TGMD-3), and a motivation questionnaire. Expert validation results showed an average feasibility of 93.19% (highly feasible). The small-scale pilot test yielded 91.5%, and the large-scale pilot test yielded 94% (highly practical). Results of the Independent t-test showed significant differences in improvement between the experimental and control groups in basic motor skills (p=0.000) and motivation (p=0.000). The N-Gain for the experimental group in basic motor skills (0.69, moderate) and motivation (0.73, high) was higher than that of the control group. The conclusion of this study is that the interactive multimedia-based physical activity model (Fun Move) is valid, practical, and effective for improving basic motor skills and physical activity motivation in students aged 10–12 years.